PENGARUH LATIHAN ONE LEG GOOD MORNING TERHADAP STABILITAS TUNGKAI PADA SISWA YANG MENGIKUTI EKSTRAKURIKULER OLAHRAGA PERMAINAN - Nandi Abdul Hadi; Hendra Rustiawan; Risma Risma; Isna Daniyati Nursasih (Universitas Galuh, 2021)
This study aims to determine how much influence one leg good morning exercise has on increasing leg muscle stability in extracurricular games sports. By the research objectives above, the authors used a pre-experimental method with